PENGGUNAAN MODEL PEMBELAJARAN LEARNING CYCLE BERBASIS PETA KONSEP PADA MATERI KESETIMBANGAN KIMIA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI SMA NEGERI 1 DAMPELAS KABUPATEN DONGGALA - Astuti, Ni Luh Murni; Tangkas, I Made; Supriadi, Supriadi (Jurnal Akademika Kimia, 2013)
Student learning outcomes will be better if the experience for themselves what really happened. They will continue to remember the events that ever happened; therefore we need a method of teaching that is oriented to students. The purpose of this research is to improve learning outcomes chemistry of students class XI at SMA Negeri 1 Dampelas using learning cycle model base map concept in equilibrium topic of chemical. The Population of this research was all students in class XI SMA Negeri 1 Dampelas which consists of 4 classes. The sample was taken 2 classes with purposive sampling technique, which are class XI IPA 2 as much as 32 students as the experiment and class XI IPA 1 as much as 32 students as the control class. Research data collection was done by using a test instrument in the form of test results of chemical equilibrium. Testing research data using statistical analysis of t-test the right side and prerequisite test is homogeneity and normality test. The median score of student learning outcomes using learning cycle methods is 17.18 while median score of student learning outcomes with conventional learning is 14.25. Based on the calculation of the t test statistic obtained t_calc= 3.71, this show that in the region of rejection H_0 is 2.00. It can be concluded that there is an increase student learning outcomes with learning cycle model base map concept than students’ conventional teaching of class XI IPA SMA Negeri 1 Dampelas on the subject of chemical equilibrium